PENANAMAN NILAI-NILAI PANCASILA DARI SEBUAH PRODUK BUDAYA - Nur Ajizah; Hasya Nurfarissar, Nazhara Ardhia; Elvina, Hilma Shafwa; Agustin, Annisa Maya; Assyadiah, Syaima Putri; Tania, Yola; Juliana, Rinto Aji; Yustira, Mochammad Galuh; Gustaman, Randy Fadillah; Rosita, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The Tasikmalaya batik industry has great potential as a producer of high-quality batik that exudes the values of Pancasila. This research aims to explore Pancasila values reflected in Tasikmalaya batik. The research method used is qualitative by means of direct observation and interviews, as well as documentation. This research provides an understanding of how the noble values of Pancasila can be interpreted and applied in the context of local culture and its contribution to the formation of national identity and the maintenance of cultural heritage. In conclusion, the results of this analysis can serve as a basis that Tasikmalaya batik reflects the values of Pancasila and recognizes the importance of continuing to support and strengthen batik in Tasikmalaya as part of efforts to build a nation based on the values of Pancasila.